BUDAYA MENANGKAP IKAN DILUBUK LARANGAN (STUDI KEARIFAN LOKAL PADA MASYARAKAT DESA PANGKALAN INDARUNG KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI) - Putri, Susyanthi Fratama; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Traditional wisdom that is local is one of the cultural heritage in society according to their respective regions that have historically been carried out by groups of people within the region itself. Lubuk Larangan is one of the local wisdom where the river is protected through the ritual or in accordance with local customs. Sungai Larangan or Lubuk Larangan are used to protect the fish are already endangered or local fish around the river. This research is located in Pangkalan Indarung village Singingi districts, Kuantan Singingi Regency, Riau Province. The purpose of this study is to know the implementation of a catch fish system on the people in Pangkalan Indarung village, to know the purpose of fishing communities in Lubuk Larangan. The theory used is the theory of local wisdom, social systems theory, and the theory of belief. The method used is qualitative data collection techniques by conducting interviews, observation, and documentation. The results showed that the culture of fishing in Lubuk Larangan on Villagers of Pangkalan Indarung is a local wisdom where fishing is done once a year, where there are the stages of implementation of the catch that is customary deliberation, mamucuak (while fishing), and the preparation equipment. The purpose of fishing once a year in Lubuk Larangan, namely as efforts to conserve endangered fish in Lubuk Larangan, economic goals and objectives of fish auction results.KeyWord: Lokal Wisdom, Lubuk Larangan, system social